The Periodontal Health Status Among Patients Attending the Periodontal Department, School of Dentistry , Facualty of Medical Science, Sulaimani University,Kurdistan Region ,Iraq - Abdulkareem Hussain Al- Saidy (Diyala Journal of Medicine, 2019)
Background: In our studys the sample included 672 patient (348 male and 324 female patients),who were attended the department of periodontics, school of dentistry University of Sulaimani during one academic year (2008-2009).The sample was divided into subgroups  according to age and sex.